Microelectronic systems 1 checkbook - Vears, R. E. (Checkbook series., 1986)
Microelectronic Systems 1 Checkbook provides coverage of the Business and Technician Education Council level 1 unit in Microelectronic Systems. However, it can be regarded as a basic textbook in microelectronic systems for a much wider range of studies. Each topic considered in the text is presented in a way that assumes the reader has little prior knowledge of electronics. The aim of the book is to provide an introduction to the concept of systems, to differentiate analogue and digital systems, and to describe the nature of microprocessor-controlled systems. An introduction to programming is.